STRATEGI PENGEMBANGAN AGRIBISNIS CABAI MERAH DI KABUPATEN SLEMAN DENGAN METODE ANALYTICAL HIERARCHY PROCESS - Lubis, Fadli Akbar; Harisudin, Mohamad; Fajarningsih, Rhina Uchyani (AGRARIS: Journal of Agribusiness and Rural Development Research, 2019)
This study aims to formulate a strategy for developing red chili agribusiness that can be applied in Sleman Regency. The study was conducted in Kalasan District since it has the highest red chili production in Sleman Regency. The method used in this research was Analytical Hierarchy Process (AHP). Based on the results of the study there were 5 aspects of strength, 5 aspects of weakness, 5 aspects of opportunity, and 5 aspects of threats. All internal and external aspects form the basis for making alternative strategies. The position of grand strategy matrix is quadrant I. There were 5 alternative strategies that are generated and included in the AHP hierarchy structure. Of the 5 alternative strategies, the 05 strategy was chosen with a priority weight value of 0.357, namely the strategy with the development of a chili auction market using digital technology.